Characterization of Cu3SnS4nanoparticles and nanostructured flowers synthesized by a microwave-refluxing method - Narongrit Tipcompor (2018)
Cu3SnS4nanoparticles and nanostructured flowers were synthesized by 100, 300, 600, and 800 W microwave refluxing of the mixture containing 3 mmol CuCl2·2H2O, 1 mmol SnCl2·2H2O, and 4 mmol thiosemicarbazide (NH2NHCSNH2) in 50ml ethylene glycol (HOCH2CH2OH). X-ray diffraction (XRD), selected area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), scanning and transmission electron microscopy (SEM and TEM), Raman analysis, and photoluminescence (PL) spectrophotometry revealed the morphology transformation of pure tetragonal Cu3SnS4with nanoparticles at 100W into three-dimensional (3D) hierarchical flower-like structure at 800 W, including the presence of 2Cu+, Cu2+, Sn4+, and 4S2-containing in the sulfide, the PL emission of the 3D hierarchical flower-like Cu3SnS4at 366 nm, and the prominent Raman peak of Cu-Sn vibration at 319 cm-1. In this research, a formation mechanism was also proposed according to the experimental results. © 2013 The Japan Society of Applied Physics.